Effect of the detonation spraying mode on the tribological properties of NiCr-Al2O3 coatings - Rakhadilov, B; Buitkenov, D. B.; Kabdykenova, E.; Zh. B. Sagdoldina, Zh. B. Sagdoldina; Zhurerova, L. G. (Eurasian Journal of Physics and Functional Materials, 2026)
The article presents the study results of detonation spraying parameters on the phase composition and tribological properties of NiCr-Al 2 O 3 powder coatings. The spraying was carried out at a ratio of the acetylene oxygen mixture O 2 /C 2 H2 =1.856. The detonation barrel filling volume with an explosive gas mixture varied from 30% to 68%. It is determined that the phase composition of the NiCr-Al 2 O 3 coatings varies depending on the degree of detonation barrel filling. With an increase in the detonation barrels filling volume, the intensity of the NiCr diffraction peaks is decreased, and the intensity of the . -Al 2 O 3 reflexes is increased, which indicates an increase in the content of the Al 2 O 3 phase. When low filling volume, there is determined a low coating density and uneven roughness. The tribological test results showed that with an increase in the detonation barrel filling volume, there is a decrease in the wear volume, which confirms the increase in the coatings wear resistance. Determined that the lowest friction coefficient was recorded in the sample obtained at the barrel filling volume 68%. The coatings high wear resistance is associated with an increase in the alpha phase volume fraction of . -Al 2 O 3 and coatings density.Recommended CitationRakhadilov, B. K.; Buitkenov, D. B.; Kabdykenova, E.; Sagdoldina, Zh. B.; and Zhurerova, L. G. (2021) "Effect of the detonation spraying mode on the tribological properties of NiCr-Al2O3 coatings," Eurasian Journal of Physics and Functional Materials: Vol. 5: No. 1, Article 5.DOI: https://doi.org/10.32523/ejpfm.2021050105